Effects of grazing on plant species composition and spatial distribution in rangelands of the Sahel - Hiernaux, Pierre H.Y. (Springer, 1998)
The effects of grazing by livestock on plant species composition and spatial distribution have been studied at Sadoré, Niger. Herbaceous species were recorded in plots of increasing size from 1/64 to 1024 m2 in ten fallow plots subjected to five different grazing treatments over the previous three years. Treatments consisted of three intensities of grazing, and of protection from grazing for either 3 or 14 years. For all treatments, the number of species fitted a normal distribution with the log (ln) of the area inventoried. However, the fit improved slightly when the model included two successive log-normal distributions respectively considered as species distribution within a patch and at the patch mosaic scale. Across treatments, the optimal sampling areas averaged 3.8 ± 1.1 m2 for the within-patch and 725 ± 113 m2 for the mosaic scale distributions. It is argued that similarity between treatments in the overall log-normal distribution resulted from compensations between the divergent trends that affected species distribution within and across patches depending on the grazing status. Long-term protection resulted in a regular spatial arrangement of highly contrasted, but internally homogeneous patches. Heavy grazing ensued the dominance of a few species in contagious patches but also left niches for scattered individuals of other species. Tests of the relative frequency of each plant species, together with the average area needed to record that species, were used to characterize specific response to grazing. A majority of species encountered in old Sahelian fallows were either fostered by grazing, indifferent or tolerant to grazing. However, more than a third of the species appeared sensitive to heavy grazing, and no relationships were found between species response to grazing and palatability.